Pengembangan Media Pembelajaran Berbasis Website “Geo Me Try” untuk Meningkatkan Pemahaman Konsep Luas Bangun Datar Peserta Didik Kelas 4 Sekolah Dasar - Veronica Prima Damayanti Bandaso; Nyoto Harjono (Jurnal Ilmiah Wahana Pendidikan, 2023)
The high interest of students in mathematics has not yet shown the achievement of maximum learning outcomes. The difficulty of students in understanding the basic concept of the area of a flat shape and the lack of supporting learning media in the teaching and learning process are factors that are not optimal in student learning outcomes. This is the main reason to create a breakthrough on this phenomenon. Through the development of learning media based on the website "Geo Me Try", the researcher intends to increase the understanding of the concept of flat shapes area concept in grade 4 at SDN Harjosari 1 Bawen in order to increase the achievement of students' learning outcomes. This research uses Research and Development (R&D) type of research. Material validation results obtained a score of 74.54%, media validation results obtained a score of 94.73%, and language validation results obtained a score of 85.71%. Normality test results showed a significance value of 0.818 > 0.05 which indicates that the data obtained are normally distributed. While the test results of Paired Sample T-test showed the results of significance 0.000 < 0.05 which shows that Geo me Try learning media influence the understanding of the broad concept of flat wake learners shown through increased pre-test and post-test results. Based on the validation results of material experts, media experts, and linguists, this learning media is a reference that the "Geo Me Try" product is feasible to use